Trinidad and Tobago : Staff Report for the Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that after emerging from a prolonged period of decline in the 1980s, the economy of Trinidad and Tobago has performed well in recent years, with steady economic growth and low inflation. Although a sizable investment boom in the energy sector should contribute to faster growth in the coming years, a serious terms-of-trade shock in 1998 limited output growth. Inflation has declined to a relatively low level, although rising food prices led to some pickup in 1998. The unemployment rate, although declining, remains high, at about 14 percent.